Status of Serum Copper and Zinc in Pre-Eclampsia (Bangladesh Journal of Medical Biochemistry, 2017)
Pre-eclampsia is a multisystem and multifactorial disease that affects both mother and fetus by endothelial dysfunction and intrauterine growth retardation. It is thought that pre-eclampsia is associated with an imbalance of increased lipid peroxides and decreased antioxidants. Dietary deficiency or excess of copper, zinc or other micronutrients play important role in the pathogenesis of pre-eclampsia because nutrients can modulate oxidative stress by increasing or decreasing free radicals or antioxidants and providing substrates for formation of free radicals.This study was carried out in the Department of Biochemistry, Sylhet MAG Osmani Medical College during the period from July 2014 to June 2015 to evaluate the status of serum copper and zinc in pre-eclamptic patients. For this study 85 age-matched women were selected and grouped as 30 pre-eclamptic patients, 27 normal pregnant and 28 nonpregnant women. serum copper and zinc level were measured in all study subjects by AAS. Data were analyzed with the help of SPSS version 17.0. Mean (±SD) level of serum copper and zinc were 1.43±0.49 mg/l and 2.43±2.89 mg/l in pre-eclamptics, while in normal pregnant women the levels were 1.51±0.47 mg/l and 2.87±2.23 mg/l and in non-pregnant women these were 0.85±0.28 mg/l and 3.70±2.61 mg/l respectively. Serum copper significantly increased in pre-eclamptics and normal pregnant women when compared with that of non-pregnant women [F (2, 82) =19.763; p